2011
DOI: 10.2147/ijwh.s23918
|View full text |Cite
|
Sign up to set email alerts
|

The Automated Breast Volume Scanner (ABVS): initial experiences in lesion detection compared with conventional handheld B-mode ultrasound: a pilot study of 50 cases

Abstract: The idea of an automated whole breast ultrasound was developed three decades ago. We present our initial experiences with the latest technical advance in this technique, the automated breast volume scanner (ABVS) ACUSON S2000™. Volume data sets were collected from 50 patients and a database containing 23 women with no detectable lesions in conventional ultrasound (BI-RADS®-US 1), 13 women with clearly benign lesions (BI-RADS®-US 2), and 14 women with known breast cancer (BI-RADS®-US 5) was created. An independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 18 publications
2
70
0
Order By: Relevance
“…Very good agreement regarding BI-RADS classification of HHUS and ABUS (25) as well as only fair agreement has been reported (26). Agreement between mammography and ABUS was poor due to a high percentage of false positive ultrasound interpretations (27).…”
Section: Discussionmentioning
confidence: 98%
“…Very good agreement regarding BI-RADS classification of HHUS and ABUS (25) as well as only fair agreement has been reported (26). Agreement between mammography and ABUS was poor due to a high percentage of false positive ultrasound interpretations (27).…”
Section: Discussionmentioning
confidence: 98%
“…The authors concluded that automated breast ultrasound is a promising modality in breast imaging. Wojcinski et al (2011) argued to the contrary that the ABVS must be regarded as an experimental technology for breast ultrasound and further studies are required. When used in the assessment of 50 lesions, the ABVS had quite low sensitivity, specificity and accuracy (52.8%, 73.2% and 66.0%, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, US scanning along the line of the mammary duct is considered to be indispensable because most breast carcinomas originate in the epithelial duct tissue and spread along the ducts (11). Based on these limitations and some reports demonstrating no explicit superiority of ABVS over US (25), ABVS cannot currently displace US for breast screening purposes and still requires further evaluation (26).…”
Section: Limitations Of Abvsmentioning
confidence: 99%
“…Although it has not yet been established as a routine screening modality, bilateral whole breast US has demonstrated diagnostic advantages over conventional US in screening asymptomatic women (9). In this study, we aimed to comparatively evaluate the latest technical advance in bilateral whole breast US-the Automated Breast Volume Scanner (ABVS) that acquires a series of consecutive B-mode pictures and reconstructs three-dimensional (3D) data sets of the entire breast volume (10)-against conventional breast US.…”
mentioning
confidence: 99%